Teachers’ opinions on the inclusion of children with Down syndrome in regular schools - Nikolić, Milena; Lozić, Matea (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Inclusive practices largely depend on teachers and their opinions about the educational inclusion of children with developmental disabilities. It has been proven that teachers’ opinion on inclusion depends on the type of developmental disability. Objectives. The primary goal of the research is to determine teacher opinions about the inclusion of children with Down syndrome in regular schools. An additional goal was to examine differences in teacher opinions concerning factors such as gender, age, length of service, experience in inclusive education, and education on how to work with children with developmental disabilities. Methods. The research sample was convenient and consisted of 70 teachers from Jajce, Bosnia and Herzegovina. The teacher’s opinion was examined with a questionnaire constructed for this research. Results. Results show that teachers have favorable opinions about the inclusion of children with Down syndrome in regular schools on overall scores. Teacher opinions differ on gender and length of service. Female teachers have a more favorable opinion than male teachers, while teachers with over thirty years of work experience have a negative one. Teacher opinions do not differ concerning age, experience in inclusive education, and education on how to work with children with developmental disabilities. Conclusion. There is a need for systematic and continuous work on inclusive policy, culture, and practice in schools, as education of teachers on the characteristics and methods of how to work with children with Down syndrome and other developmental disabilities